Multivariate relationships between graft detachment after DMEK and twelve pre/perioperative factors - Delphine Metz; Grace Gan; Christophe Goetz; Yinka Zevering; Rémi Moskwa; Jean-Charles Vermion; Jean-Marc Perone (Scientific Reports)
Abstract This study aimed to identify pre/perioperative risk factors for graft detachment after Descemet membrane endothelial keratoplasty (DMEK). Hierarchical multivariate analysis was conducted on consecutive adults with Fuchs endothelial corneal dystrophy or pseudophakic bullous keratopathy who underwent pseudophakic- or triple-DMEK in 2014–2022 and were followed for 3 months. Significant graft detachment was defined as exceeding 20% of the graft or affecting the graft center. Twelve pre/perioperative factors were included. Of the 170 eyes (125 patients, median age 73 years, 65% women), 15% displayed significant graft detachment. Significant graft detachment was predicted by use of air rather than sulfur hexafluoride (SF6) for endotamponade (Odds Ratio [OR] = 0.20, 95% confidence intervals [95%CIs] = 0.05–0.91, p = 0.04) and patient age above 72.5 years (OR = 2.84, 95%CIs = 1.02–7.88, p = 0.046). Thus, SF6 use reduces DMEK-graft detachment. Whether older patients demonstrate more graft detachment because they have difficulty remaining supine after surgery or have inherent age-related corneal fragilities that hamper graft take remains to be determined.